Modeling for determining the superiority of Holstein bulls as frozen semen producer and genetic source for milk production - Argiris, A.; Santoso, S. I.; Ondho, Y. S.; Kurnianto, E. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
The objective of this study was to develop models for determination the superiority of Holstein bulls as a producer of frozen semen and inheritance of the genetic traits of milk production. The ability of the bull to produce frozen semen per years was analyzed descriptively. Reproductive efficiency of frozen semen in artificial insemination was calculated by service per conception (S/C). Estimation sire breeding value for milk production was calculated by contemporary comparison (CC) method. Model of superiority bulls was analyzed by Structural Equation Model with Partial Least Square method (SEM-PLS). Total average production of frozen semen was 23,109±14,970 doses/year. The average S/C was 2.83. The CC value ranged from -1,865.7 until +1,636.3. Potency of milk production resulted from lactation cow offspring per bulls ranged from 951,749.2 to 52,347,822.9 liters per year. The economic value of bulls based on the potency milk production of offspring ranges from IDR 4,758,745,999 to IDR 261,739,114,505. The superiority of bulls was affected significantly (P<0.05) by frozen semen production, reproductive efficiency and average milk production of daughter cows (DC) as much as 0.59, -0.53 and 0.33, respectively. In conclusion, the superiority of bull can be explained about 78.3% by the production of frozen semen production, reproductive efficiency and milk production of offspring.